Characterization of Local Sands for Possible Use as Proppant - Suhaila binti Muhamad, Suhaila (Universiti Teknologi Petronas, 2009)
This paper presents results on literature and experimental works on Malaysia local sand for possible use as proppant specifically local sand resourced from Terengganu area. Proppant is a granular material that is mixed with fracturing fluid to hold fractures open after a hydraulic fracturing treatment is conducted in a formation. The oilfield developers in Malaysia obtain the supply of proppant from foreign suppliers as there is still no local proppant manufacturer and supplier in Malaysia. This is one of the causes of high well stimulation costs. This project includes the study on the characteristics of proppants and research on the laboratory experiments in testing the characteristics of Terengganu sand as proppant. The sand sample from the desired area are tested by its; particle size distribution, density, roundness and sphericity, turbidity, mineralogy, crush resistance, permeability, and conductivity. The sand characteristics should meet the specifications set by American Petroleum Institute (API) or International Standard Organization (ISO) for commercial proppant. The results obtained from the analyses are compared to the existing sand based proppant in the market. The size distribution, turbidity and bulk density of Terengganu sand agree with the commercial proppant. Even though Terengganu sand do not completely surpass the typical sand based proppant at certain characteristics (roundness, sphericity, crush resistance), they show promising results and meet some of the API and ISO requirements. Recommendations are also proposed in this paper for future improvement in increasing the quality of project results